Convolutional neural network identification of galaxy post-mergers in UNIONS using IllustrisTNG. Issue 1 (19th March 2021) - Bickley, Robert W; Bottrell, Connor; Hani, Maan H; Ellison, Sara L; Teimoorinia, Hossen; Yi, Kwang Moo; Wilkinson, Scott; Gwyn, Stephen; Hudson, Michael J
ABSTRACT: The Canada–France Imaging Survey (CFIS) will consist of deep, high-resolution r -band imaging over ∼5000 deg 2 of the sky, representing a first-rate opportunity to identify recently merged galaxies. Because of the large number of galaxies in CFIS, we investigate the use of a convolutional neural network (CNN) for automated merger classification. Training samples of post-merger and isolated galaxy images are generated from the IllustrisTNG simulation processed with the observational realism code RealSim . The CNN's overall classification accuracy is 88 per cent, remaining stable over a wide range of intrinsic and environmental parameters. We generate a mock galaxy survey from IllustrisTNG in order to explore the expected purity of post-merger samples identified by the CNN. Despite the CNN's good performance in training, the intrinsic rarity of post-mergers leads to a sample that is only ∼6 per cent pure when the default decision threshold is used. We investigate trade-offs in purity and completeness with a variable decision threshold and find that we recover the statistical distribution of merger-induced star formation rate enhancements. Finally, the performance of the CNN is compared with both traditional automated methods and human classifiers. The CNN is shown to outperform Gini–M20 and asymmetry methods by an order of magnitude in post-merger sample purity on the mock survey data. Although the CNN outperforms the human classifiers on sample completeness, the purity of the post-merger sample identified by humans is frequently higher, indicating that a hybrid approach to classifications may be an effective solution to merger classifications in large surveys.